EFFICACY OF INFLIXIMAB IN THERAPY OF REFRACTORY JUVENILE RHEUMATOID ARTHRITIS (JRA)EFFICACY OF INFLIXIMAB IN THERAPY OF REFRACTORY JUVENILE RHEUMATOID ARTHRITIS (JRA) - E.I. Alexeeva; A.M. Alekseeva; T.M. Bzarova; S.I. Valieva; E.Yu. Afonina ("Paediatrician" Publishers LLC, 2006)
The purpose of this open study was to evaluate efficacy and safety of infliximab, an antiatnfa ?monoclonal antibody, in 37 children with juvenile idiopathic arthritis (JIA). Group 1 comprised 16 patients with severe longaterm jia with systemic onset. Group 2 comprised 21 patients with oligoa and polyarticular JIA. Groups were matched in demographic features. The follow up period has ranged between 6 weeks and 2 years. All children received infliximab and concomitant D mard therapy, 3 of them received oral glucocorticoids. Inflixa imab with a mean dose of 6,5 ± 0,3 mg/kg was administered intravenously at baseline, 2, 6 and every 8 week. Infliximab has shown statistically significant improvement (p < 0,01) in all patients with early oligoa and polyarticular JIA (group 2). Remission following the second infusion (at the 3 week of observation) has been registered in all patients with oligoa and polyarticular jia, meanwhile in patients with systemic JIA remission has been registered only in 2 cases at a time of 7 months of treatment with infliximab. Eight (50%) patients from group 1 and 2 children (9,5%) from group 2 discontinued infliximab due to inefficacy. 5 (24%) of patients from group 2 developed side effects that led to infliximab discontinuation. Therefore, the therapy with infliximab has proved to be sound, safe and effective with best results in patients with oligoa and polyarticular jia.Key words: juvenile rheumatoid arthritis, infliximab, children.